Are hospitalized Parkinson's disease patients more likely to carry a do-not-resuscitate order?. (March 2017) - Mahajan, Abhimanyu; Patel, Achint; Nadkarni, Girish; Sidiropoulos, Christos
Highlights: We used the largest public national inpatient database in the United States. We analyzed 12, 700, 000 hospitalizations with age ⩾65 hospitalized in 2012. Proportion of DNR utilization was higher among hospitalizations in PD patients. DNR utilization odds increased with overall disease burden. Abstract: While DNR utilization is a complex subjective phenomenon, the effect of such a decision can collectively influence attitudes of care. The role of palliative care in advanced PD has been under appreciated. We reviewed the Healthcare Cost and Utilization Project's National Inpatient Sample (NIS) database from 2012 for all hospitalizations ⩾65 years. We identified PD by using ICD-9-CM code 332.0 and DNR status with ICD code – V49.86 entered during the same admission as a secondary diagnosis. We estimated risk of mortality by the 3 M™ All Patient Refined DRG (APR DRG) classification System and generated multivariate regression models to assess associations between DNR and PD after adjusting for confounders. Finally, we tested for interaction by risk of mortality. We analyzed 12, 700, 000 hospitalizations with age ⩾65 years in 2012, of which 246625 (1.94%) pts had PD. Proportion of DNR utilization was higher among PD patients vs. those without, 20895 (8.47%) vs. 723090 (5.8%) ( p  < 0.01). In multivariable regression analysis, PD patients were associated with higher odds of DNR utilization [Adjusted Odds ratio (aOR): 1.26, 95% CI: 1.21, 1.30, p  < 0.001]. Finally, the odds of DNR utilization increased significantly with APR-DRG stage [aOR: 1 vs. 1.61 (Stage 2) vs. 2.46 (Stage 3) vs. 3.61 (Stage 4); p  < 0.0001]. PD patients have higher odds of DNR utilization than the general population, which worsens with increasing objective risk of mortality. This is likely correlated with perception of end of life and importance of QOL with increasing severity of overall illness.